YIELD AND MINERAL COMPOSITION OF GRAPEVINE AS AFFECTED BY MAGNESIUM AND IRON FOLIAR NUTRITION - Hristina Poposka; Dusko Mukaetov; Dusko Nedelkovski (Goce Delcev University of Štip, 2019)
The aim of this study was to evaluate foliar fertilizers (Magni mag helat and Magni fer helat) effects on yield, quality parameters and nutrient contents of the leaves of vine cultivar Cardinal in comparison to control variant (without foliar fertilizer). Field trials has been organised according the method of random block system with three variants (including control variant I) in three repetitions. Foliar fertilizers were applied in concentration of 0.5 %, four times during the vegetation period (before and after blooming, buckshot berries and version). Results for 3 years indicated that Mg and Fe fertilizers application affected the yield of grape and its quality. Fertilized Variant III had higher average yield with 14.87 t/ha. Foliar fertilizing with Fe has significant effect on increasing of: total cluster weight, berries weight per cluster and percentage of berries. Treated variants had a lower weight of skin and seeds, compared with the control. A substantial influence of foliar fertilizers on analysed element contents in leaves has been identified, also. The 3-years average content of macro and micro elements showed higher content of P (0.35 %), Ca (3.03 %), N (2.25 %), Mn (133.24 mg/kg) and Cu (18.18 mg/kg), at Variant II. Results of leaf tissue confirmed some antagonistic relations between analysed elements, like: Fe/P, Mg/K and Fe/Mn.
Keywords: Cardinal, berries, element, fertilization, quality